2020
DOI: 10.1002/anie.202005109
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Synthesis of Aryl Amines from Phenols Utilizing Integrated Packed‐Bed Flow Systems

Abstract: Aryl amines are important pharmaceutical intermediates among other numerous applications. Herein, an environmentally benign route and novel approach to aryl amine synthesis using dehydrative amination of phenols with amines and styrene under continuous‐flow conditions was developed. Inexpensive and readily available phenols were efficiently converted into the corresponding aryl amines, with small amounts of easily removable co‐products (i.e., H2O and alkanes), in multistep continuous‐flow reactors in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Despite these advantages, this type of reaction has rarely been applied for the synthesis of amino acid compounds. Recently, we reported the continuous synthesis of aryl amines from cyclohexanones, which were prepared from the hydrogenation of phenols, by utilizing an integrated packed‐bed flow system [25] . In this protocol, amines and cyclohexanones, with styrene as a neutral hydrogen scavenger, were passed through a column reactor containing a heterogenous Pd(OH) 2 /C catalyst to afford the corresponding aryl amines in good to excellent yields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advantages, this type of reaction has rarely been applied for the synthesis of amino acid compounds. Recently, we reported the continuous synthesis of aryl amines from cyclohexanones, which were prepared from the hydrogenation of phenols, by utilizing an integrated packed‐bed flow system [25] . In this protocol, amines and cyclohexanones, with styrene as a neutral hydrogen scavenger, were passed through a column reactor containing a heterogenous Pd(OH) 2 /C catalyst to afford the corresponding aryl amines in good to excellent yields.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported the continuous synthesis of aryl amines from cyclohexanones, which were prepared from the hydrogenation of phenols, by utilizing an integrated packed-bed flow system. [25] In this protocol, amines and cyclohexanones, with styrene as a neutral hydrogen scavenger, were passed through a column reactor containing a heterogenous Pd(OH) 2 /C catalyst to afford the corresponding aryl amines in good to excellent yields. This flow method was applicable for the stereoretentive N-arylation of l-phenylalanine methyl ester.…”
mentioning
confidence: 99%
“…A multistep continuous flow reactor using heterogeneous Pd catalysts was established for the amination of phenols. [50] In the first stage where hydrogenation took place, Pd/C catalysts were packed in the column and in the second stage where condensation and dehydrogenation took place, Pd(OH) 2 /C were packed in the column. The integrated flow reactor afforded high conversions, productivity (up to 0.31 kg L À 1 day À 1 ) and enantioselectivity and was able to smoothly operate for one week.…”
Section: Packed Catalysts For Multistep Reactionsmentioning
confidence: 99%
“…2,67,78 Notably, such a transformation could also be realized in a continuous-flow reactor as reported by Kobayashi and co-workers recently. 77 As we further studied such direct phenol-amine coupling reactions with other substrates such as pyrrolidine, we found that, in the presence of a stronger hydride donor (NaBH 4 ) and a stronger acid (triflic acid), the pyrrolidine motif would be selectively rearomatized instead of the cyclohexyl moiety to afford N-cyclohexyl pyrrole (Scheme 13), 68 rather than the normal coupling product N-phenyl pyrrolidine as shown in Scheme 12. 2 This coupling reaction featured a formal aromaticity-transfer since the aromaticity of phenol was formally transferred to pyrrolidine with phenol being reduced to cyclohexyl motif and pyrrolidine being oxidized to pyrrole, highlighting good atom-and redox-efficiencies.…”
Section: Formal Reductive Couplingmentioning
confidence: 99%
“…Subsequently, anilines could be formed by the rearomatization of imine (or enamine) intermediates via dehydrogenation catalyzed by Pd/C. Overall, the mechanism involved a “dearomatization-condensation-rearomatization” sequence (Scheme b). ,, Notably, such a transformation could also be realized in a continuous-flow reactor as reported by Kobayashi and co-workers recently …”
Section: Formal Redox-neutral Coupling (Formal Phenol Direct Amination)mentioning
confidence: 99%